Welcome to European Journal of Chemistry - Arslan, Hakan (European Journal of Chemistry, 2010)
On behalf of the editorial team, welcome to European Journal of Chemistry. European Journal of Chemistry is a recently established journal publishing original research papers, reviews and technical notes on the topics of Analytical Chemistry, Inorganic Chemistry, Organic and Bioorganic Chemistry, Biochemistry, Theoretical and Applied Physical Chemistry, Pharmaceutical Chemistry, Applied and Materials Chemistry, Chemical Technology, Agro Chemical Technology, Pharmaceutical Technology, Colloid Chemistry, Interfacial Chemistry, Surface Chemistry, Chemical Engineering, Green Chemistry, etc. Our aim is to encourage scientists to publish their theoretical and experimental details, while interacting and exchanging valuable information with each other. European Journal of Chemistry is an Open Access Journal. The published articles in European Journal of Chemistry are freely accessible via the Internet for immediate worldwide, open access to the full text of research articles for the best interests of the scientific community. All interested readers can read, download, and print any Open Access article at no cost. There are no subscription fees for European Journal of Chemistry. This journal accepts original research and review papers as well as letters in all areas of chemistry. A manuscript submitted to the journal for publication should be original. It should not have been previously published and should not be under consideration for publication elsewhere. All published research articles in this journal have undergone rigorous peer review, based on initial editor screening and anonymised refereeing by at least two expert reviewers. Authors are encouraged to suggest referees for their work. The journal is published print and online and articles are available as online rapidly after acceptance. The published articles are expected to receive high citations as the journal develops and reaches prominence in the field. I expect that European Journal of Chemistry will attract manuscripts of the highest quality which are of the greatest possible benefit to readers. We look forward to receiving your submissions. Please do not hesitate to contact the Editor, if you would like to discuss the suitability of your contribution to European Journal of Chemistry. Dr. Hakan Arslan Founding and Editor-in-Chief European Journal of Chemistry www.eurjchem.com